JunD/HBZ enhances HBZ enhances HTLV-1 antisense transcription - Peloponese, Jean-Marie; Lemasson, Isabelle; Barbeau, Benoit; Mesnard, Jean-Michel (My University, 2011)
Infection with the human T-cell leukemia virus type 1 (HTLV-1) results in a variety of diseases including adult T-cell leukemia (ATL), a fatal malignancy characterized by the uncontrolled proliferation of virally infected CD4+ T cells. The HTLV-1 basic leucine zipper factor (HBZ) is believed to contribute to development and maintenance of ATL. Unlike the other HTLV-1 genes, the hbz gene is encoded on the complementary strand of the provirus and therefore is not under direct control of the promoter within the 5′ long terminal repeat (LTR) of the provirus. This promoter can undergo inactivating genetic or epigenetic changes during the course of ATL that eliminates expression of all viral genes except that of hbz. In contrast, repressive modifications are not known to occur on the hbz promoter located in the 3′ LTR, and hbz expression has been consistently detected in all ATL patient samples. Although Sp1 regulates basal transcription from the HBZ promoter, other factors that activate transcription remain undefined. In this study, we used a proviral reporter construct deleted of the 5′ LTR to show that HBZ upregulates its own expression through cooperation with JunD. Activation of antisense transcription was apparent in serum-deprived cells in which the level of JunD was elevated, and elimination of JunD expression by gene knockout or shRNA-mediated knockdown abrogated this effect. Activation through HBZ and JunD additionally required Sp1 binding at the hbz promoter. These data favor a model in which JunD is recruited to the promoter through Sp1, where it heterodimerizes with HBZ thereby enhancing its activity. Separately, hbz gene expression led to an increase in JunD abundance, and this effect correlated with emergence of features of transformed cells in immortalized fibroblasts. Overall, our results suggest that JunD represents a novel therapeutic target for the treatment of ATL.